Conceptual Evolution of Innovation and Entrepreneurship in SME Sustainability Research: A Bibliometric Analysis - Syarifa Rahmi; Rino Rino; Yunia Wardi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This systematic literature review examines the role of innovation and entrepreneurship in advancing sustainability within small and medium-sized enterprises (SMEs). A total of 62 articles were analyzed to identify key themes, emerging trends, and research gaps concerning the interplay among innovation, entrepreneurship, and sustainability. The findings indicate that innovation encompassing technological, process, and social dimensionsserves as a critical driver of resource efficiency and environmentally responsible practices. Entrepreneurial mindsets and behaviors further support the identification and pursuit of sustainable business opportunities that balance economic, social, and environmental objectives. The review also highlights several barriers, including limited financial capacity, restricted access to technology, and risk aversion. Conversely, supportive policy frameworks, stakeholder engagement, and knowledge networks strengthen the implementation of sustainability practices. Contextual factors such as industry characteristics, firm size, geographic location, and institutional settings significantly influence sustainability outcomes. Overall, this review underscores the importance of innovation and entrepreneurship as essential foundations for SMEs in achieving long-term sustainability.